Development of a Model of Strategic Priorities for Sustainable Development of Rural Areas in Kazakhstan until 2030. Example of the East Kazakhstan Region - NURALINA, Kalamkas; BAIZHOLOVA, Raisa; ABENOV, Yergali; MUKHIYAYEVA, Dinara; MOLDAKENOVA, Yerkezhan (Journal of Environmental Management and Tourism; Vol 14 No 5 (2023): JEMT, Volume XIV, Issue 5(69), Fall 2023DO - 10.14505/jemt.v14.5(69).10, 2023)
The problems of sustainable development have been actively investigated by the scientific community. However, due to the difficulties of implementing this concept in practice, the focus of research is increasingly shifted to the study of certain aspects affecting the sustainable development of territories. In particular, this concerns the sustainable development of agriculture and rural areas, especially in socio-demographic, economic, and institutional aspects. The purpose of the article is to develop a model of strategic priorities for the sustainable development of rural areas in Kazakhstan until 2030. The article presents a model of strategic priorities for sustainable development of rural areas in the East Kazakhstan region according to socio-demographic and economic vectors, as well as institutional support with appropriate strategic goals, indicators, and target values. Solving the problem of sustainable development of rural territories is a long-term task, which can be achieved through the development of the economy of territories. The transition of rural territories to a sustainable development strategy will ensure effective farming, orientation to high standards of social protection of the rural population, multifunctional use of rural territories, preservation of the quality of the natural environment, and adaptation of institutional mechanisms to the functioning of rural agriculture and rural development.